Usulan Rancangan Kursi Kerja yang Ergonomis Bagi Pengrajin Batik Tulis pada UMKM Batik Rajasamas Maos - Anisha Dian Iswahyuni (Pusat Riset dan Inovasi Nasional, 2024)
UMKM Batik Rajasamas Maos produces various types of batik, one of which is hand-written batik. The work process for making written batik at UMKM Batik Rajasamas Maos is still done manually and does not pay attention to a comfortable working environment for workers. In the science of ergonomics there are important things about working posture and the movements carried out by humans. This research was conducted to make a proposal for a chair design for batik craftsmen using the RULA (Rapid Upper Limb Assessment) method analysis. The RULA method is a fast method for assessing upper body posture. After carrying out this research, it is known that the ergonomic risk level of batik craftsmen's working posture requires further investigation and in the future, replacing the old work chair with a new work chair designed based on an anthropometric approach. A new work chair that has been designed based on an anthropometric approach.